Peranan Koperasi Sangosay Dalam Pengembangan Sektor Usaha Mikro Kecil Dan Menengah (UMKM) Di Cabang Maumere - Clara Rosmyati Tia; Wilhelmina Mitan; Pipiet Niken Aurelia (Universitas 45 Surabaya, 2023)
This study aims to analyze the Role of the Sangosay Credit Cooperative in the Development of the Micro, Small and Medium Enterprises (MSMEs) Sector in the Maumere Branch. The method used in this study is descriptive qualitative with primary data and secondary data as data sources. Data collection techniques in the form of observation, interviews, and documentation using descriptive qualitative data analysis techniques. The results of the study show that the Maumere Branch Sangosay Credit Cooperative does not only act as a financial institution to assist Micro, Small and Medium Enterprises (MSMEs) in obtaining business capital but also as a money depository institution and as a facilitator. The role as a facilitator includes management facilitators in terms of providing socialization and assistance to MSME players, but the Sangosay Credit Cooperative has not yet carried out its role as a marketing facilitator and financial facilitator.